The Alpine Campaign of 1799 as a Stepping Stone to a Doctrine of Mountain Warfare - Statiev, Alexander (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2019)
The Russian Imperial Army fought for the first time in the mountains in 1799, when Alexander Suvorov led his corps from Italy across the Swiss Alps to join the Russian forces at Zurich and expel the French Army from Switzerland. His soldiers were skilled professionals who had won an impressive series of battles in Italy against the French. Suvorov did not anticipate problems in the Alps, being convinced that he would easily sweep away the small French garrisons deployed on his way. Yet, because of inexperience in mountain warfare, Suvorov’s corps struggled against enormous strategic, tactical, and logistical chal- lenges, lost half of its manpower and failed to attain its goals. The Swiss trek shows that mountain warfare defies amateurism, dilettantism and spontaneity. Even though mountains are located on the verges of Rus- sia, the Russian and then Soviet armies ignored the peculiarities of mountain warfare and fought every new campaign in the mountains the same way they would fight on the plains, with predictably dire consequences.